2019
DOI: 10.1016/j.foodhyd.2019.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic atomization of Balangu (Lallemantia royleana) seed gum for the fast-release of Mentha longifolia L. essential oil: Characterization of nano-capsules and modeling the kinetics of release

Abstract: Table 1. The surface tension of pure Balangu seed gum and various Oil/Water emulsions. Treatment Sample Surface tension (mN/m) Pure gum 0.25% Balangu gum 68.24±0.05 a 0.5% Balangu gum 60.77±0.04 b PVA free 0.25% BG+0.06%T-20+EO 39.36±0.6 a 0.25% BG+0.08%T-20+EO 38.21±0.07 b 0.25% BG+0.1%T-20+EO 38.18±0.3b 0.5% BG+0.06%T-20+EO 35.02±0.02 c 0.5% BG+0.08%T-20+EO 33.45±0.05 d 0.5% BG+0.1%T-20+EO 31.70±0.04 e Constant gum 0.25%BG+0.5%PVA+0.08%T-20+EO 39.89±0.04 a 0.25%BG+1%PVA+0.08%T-20+EO 37.05±0.06 c 0.25%BG+2%PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(31 citation statements)
references
References 61 publications
3
27
0
1
Order By: Relevance
“…In this study, the amount of OPO released relative to the composite film within 300 h was recorded. The results in Figure 7 show that the relative release concentration of OPO was the highest at a ratio of 5/5, and over time it would last longer to maintain a higher release concentration without sudden release after 120 h. This phenomenon was the same as the explosive release of essential oils which was recorded by some scholars [55]. This indicated that the composite film formed by nanoencapsulation of OPO in the food industry had controllability for the release of OPO, and the surfactants Span 80 may increase the fluidity between the components and regulate the permeation rate of OPO [56].…”
Section: Resultssupporting
confidence: 53%
“…In this study, the amount of OPO released relative to the composite film within 300 h was recorded. The results in Figure 7 show that the relative release concentration of OPO was the highest at a ratio of 5/5, and over time it would last longer to maintain a higher release concentration without sudden release after 120 h. This phenomenon was the same as the explosive release of essential oils which was recorded by some scholars [55]. This indicated that the composite film formed by nanoencapsulation of OPO in the food industry had controllability for the release of OPO, and the surfactants Span 80 may increase the fluidity between the components and regulate the permeation rate of OPO [56].…”
Section: Resultssupporting
confidence: 53%
“…A difference in fatty acid chain lengths of lipids leaded to structural imperfections of matrices and presents extra space for encapsulation of active ingredient. Surfactant can stabilize the formulation and also increase an entrapment of the active ingredient into the lipid matrix of the NLC system [23, 26].…”
Section: Resultsmentioning
confidence: 99%
“…The active compound release mechanism from lipid nanoparticle matrix can be categorised either in diffusional or erosion controlled, or could be administered by both mechanisms [35]. Consequently, to study the mechanism and acquire a clear view of the Res release from NLC system, the experimental data obtained from the release profile was fitted to various mathematical models, for example zero‐order, first order, Higuchi, Hopfenberg, Hixson‐Crowell, Quadratic, Korsmeyer‐Peppas, and Weibull [23, 35] were selected to anticipate the release behaviour from NLC formulation. Generally, these models have the capability to transform the active compound release profile in a mathematical function associated with the physicochemical characteristics of the formulation [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of cooking loss was improved according to Rezaeinia et al [11]. Take appropriate amount of meat pieces x0, put them into the cooking bag and seal them, and put them into water at 75°C.…”
Section: Study On the Preservation Effect Of Compound Preservative On Chilledmentioning
confidence: 99%